Comparative Analysis of Factory Parts Supplier Performance Using the Vendor Performance Rating and Analytic Hierarchy Process Methods (Case Study of PT Pupuk Iskandar Muda) - Deny Novrizal; Edy Fradinata; Irwansyah; Yuwaldi Away; Iskandar Hasanuddin (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The availability of spare parts is the main factor that must be considered in the maintenance process so that maintenance can be carried out as planned. The availability of spare parts really depends on the procurement process which involves many parties including suppliers who are an important part of supply chain management in a company. Supplier assessment or evaluation in several previous studies was studied using several methods, including the Vendor Performance Rating ("VPR") method which is part of the SAP application and also the Analytic Hierarchy Process ("AHP") method. The aim of this research is to determine the weight of performance priorities in determining suppliers for factory spare parts procurement using the VPR and AHP methods. The objects of this research are factory spare parts suppliers registered with PT Pupuk Iskandar Muda, namely CV A, CV B, CV C, CV D and CV E. Based on the results of the analysis using the VPR method, it is CV A got the highest average score of 89.05 (weight percentage 23%), and the lowest was CV C with an average value of 78.17 (weight percentage 16%). The results using the AHP method are the highest as well as CV A 30% with a weight value of 0.3047, and the lowest is also CV C 9% with a weight value of 0.0822. Judging from these two methods, suppliers who perform well and poorly are the same.